Destino profissional de egressos dos Cursos de Licenciatura em Geografia da Universidade Federal de Minas Gerais - Ana Maria Simoes Coelho (2017)
The research object of this thesis is the professional destination of graduates of the teaching education courses (day time and nocturnal) for Geography teachers of the Federal University of Minas Gerais (UFMG), formed in the period of 2003 to 2013. Considering the low attractiveness of the teaching profession in Brazil, today, due to the low salaries and the social discredit, besides the presently difficult conditions for teaching, this research analyzes what happens with these graduates after they finish their course. The main objective is to understand if they are, in fact, exercising the profession of teachers of Geography in basic education, what they have done to keep themselves as teachers, or, instead, why they did not join the profession or decided to abandon it, under what circumstances they did it and what they are doing for a living. The research also focused on the training provided by the university course they completed. The information for the survey was obtained through the application of a questionnaire, sent to the graduates of the period of interest via Internet, by the Google Docs system. Of the 163 teachers who answered the questionnaire, about one-third of the graduates contacted, nine were also interviewed in order to deepen certain topics. The question of the professional status of the teaching profession has been revisited in the light of the contributions of the Sociology of Professions and also of the authors who criticize this line of analysis, as well as the dichotomy professionalization versus proletarianization, seeking other possibilities to understand the questions involved and to contribute to the debate. The importance of the discussion about teacher professionality and other specificities of the teaching profession was also reinforced. In this sense, I question whether achieving the allegedly sought-after professionalization is an advantage for the faculty or whether it would be best to seek the reaffirmation of the profession on its own bases, without seeking to adjust to a model that has repeatedly shown to be inadequate for the teaching profession. The search for conforming to a model which premises are distant from the reality of the teaching profession ends up contributing to the devaluation of teachers, and therefore, to the low attractiveness and the withdrawal from the profession. 70% of this research participants are graduates of the nocturnal course. The survey revealed a general socioeconomic profile in which men and women appear in equivalent proportions, predominantly aged between 31 and 35 years (41%), unmarried (53%), black (55%), who perceive themselves mostly as belonging to the lower middle class, with 49% of them being the main family income providers. The majority (70%) attended most of the basic education in public schools, 64% took three to five years to enter university after finishing high school, 61% have close relatives who are teachers, 38% also took the baccalaureate, of which 82% finished first the teaching education course. 51% received some type of scholarship, 73% had to work during graduation and 46% had some professional experience as teachers of basic education during their undergraduate degree. As for the professional trajectory, three profiles of graduates were found: those who did not enroll in teaching (34%), those who entered the teaching profession and then left it (23%), and those who became teachers and remain in teaching 42%). Non-entry into the teaching profession was due in most cases to the fact that the graduates were already engaged in a better paid activity and preferred not to leave it, not only because of the low salaries paid to teachers, but also because of the difficult conditions for teaching. The research revealed that dropping out of teaching occurs mainly among beginner teachers, who have up to three years of profession, usually due to difficulties encountered in the exercise of teaching.